Analisis Titik Impas Pada Agroindustri Tahu (Studi Kasus Pada Seorang Perajin di Desa Rancaekek Kulon Kecamatan Rancaekek Kabupaten Bandung) - Fatyah Rahmi; Samsul Arifin; Tito Hardiyanto (Jurnal Dimamu, 2023)
This study aims to: (1) determine the production costs, revenues, and income of tofu agroindustry in one production process for a craftsman in Rancaekek Kulon Village, Rancaekek District, Bandung Regency. (2) Knowing the value of the tofu agro-industry break-even point in one production process for a craftsman in Rancaekek Kulon Village, Rancaekek District, Bandung Regency. The type of research used is a case study method, the sample of respondents was taken purposively on a tofu craftsman in Rancaekek Kulon Village, Rancaekek District, Bandung Regency. Data analysis was carried out by knowing the costs, revenues, and incomes obtained from the tofu agroindustry and the value of the break-even point of acceptance, the break-even point of production, and the break-even point of product prices. The results showed that: (1) The amount of production costs in the tofu agroindustry in Rancaekek Kulon Village per one production process was Rp. 1,467,175,61 and the revenue earned per one production process is Rp. 2,304,000, so that the income earned by the craftsmen is Rp. 836,824.39 in one production process. (2) The value of the break-even point of receipts is Rp. 18,280,33, the break-even point of production is 45,7 pieces and the break-even point for the product price is Rp. 254.72/piece.